Ionic liquids: A pharmaceutical perspective - M. Lúcia M.F.S. Saraiva (2014)
In the last decades, ionic liquids (ILs) progressed from chemical curiosities to interesting biological compounds apprehending the attention of researchers of distinct areas, from chemistry to pharmacology. Initially, ILs were explored as materials for diverse applications due to the possibility of synthesize compounds with targeted chemical properties combined with selected physical properties. More recently, the emergence of ILs with biological activity revolutionized the scientific focus of these compounds and opened interesting perspectives regarding their pharmaceutical application. From the pharmaceutical point of view, an IL approach, in the design of novel active pharmaceutical ingredients (APIs), appears to be appropriate as it enables the chemical manipulation of the compounds with specific objectives related with the manufacturing process, the stability of the formulation, bioavailability and eventual adverse effects. Furthermore, even though crystallinity confers advantages during isolation, processing and storage of the drug, it is known that solid forms of APIs often suffer from low solubility and polymorphic conversion which can influence negatively the bioavailability of the drug and ultimately its therapeutic effect. On a distinct perspective, the possibility of engineering the properties of ILs by manipulating anion-cation combinations, in association with their solvent properties and in some cases water-miscibility, are considered promising characteristics regarding the applicability of ILs as solvents or carriers of pharmaceutical drugs. In this chapter it is intended to expose the pharmaceutical potential of ILs through the discussion of their utilization either as APIs or solvents/carriers of pharmaceutical drugs. The discussion will be centered on the benefits of the IL approach for the development of novel drug candidates considering not only physico-chemical aspects but also the pharmaceutical profile of the developed active pharmaceutical ingredients with IL properties. Considering the utilization of ILs as solvents of drugs or as part of drug delivery systems, it is anticipated that the discussion will be focused on the efficiency and toxicity of the systems and on their influence on the pharmacokinetics and pharmacodynamics of the vehiculated drugs. It is also planned to debate the motivations for the pharmaceutical usage of ILs as well as their peculiar properties that launched them in this context. Currently, the pharmaceutical utilization of ILs is one of the most relevant applications of these solvents, with impact on the safety and effectiveness of the involved processes and with benefits in terms of pharmaceutical formulations and pharmacological activity. It is our belief that this chapter is adequate for the book in project and can greatly enhance its acceptance and interest by readers in distinct research areas.